2001
DOI: 10.1007/s11661-001-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of tensile property and microstructure in friction stir weld of 6063 aluminum

Abstract: Dominant microstructural factors governing the global tensile properties of a friction-stir-welded joint of 6063 aluminum were examined by estimating distribution of local tensile properties corresponding to local microstructure and hardness. Yield and ultimate tensile strengths of the as-welded weld were significantly lower than those of the base material. Postweld aging and postweld solution heattreatment and aging (SHTA) restored the strengths of the weld to the levels of the base material. Elongation was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
136
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(153 citation statements)
references
References 29 publications
15
136
1
1
Order By: Relevance
“…A softened region has been formed in the joints of 2017-T351 aluminum alloy due to the effect of friction heat as occurred in the joints of other heat-treatable aluminum alloys [7,[21][22][23]. The tensile properties and fracture locations of the joints are, to a large extent, dependent on the welding defects and hardness distributions of the joints, and which, in turn, on the welding parameters [6,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A softened region has been formed in the joints of 2017-T351 aluminum alloy due to the effect of friction heat as occurred in the joints of other heat-treatable aluminum alloys [7,[21][22][23]. The tensile properties and fracture locations of the joints are, to a large extent, dependent on the welding defects and hardness distributions of the joints, and which, in turn, on the welding parameters [6,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the FSW process can be used to weld heat-treatable aluminum alloys in order to obtain high-quality joints [1][2][3][4]. However, many studies on the microstructural characteristics and mechanical properties of the friction-stir-welded joints have indicated that FSW gives rise to softening in the joints of the heat-treatable aluminum alloys such as 2014-T651 [5], 2024-T3 [6,7], 2024-T351 [8,9], 2024-T6 [10,11], 2195-T8 [12,13], 6061-T5 [14,15], 6061-T6 [8,[16][17][18], 6063-T5 [19][20][21], 6082-T5 [22], 7075-T651 [23] and 7475-T76 [7] because of the dissolution or growth of strengthening pre-cipitates during the welding thermal cycle, thus resulting in the degradation of the mechanical properties of the joints. Hence, it is important to study the effects of welding process parameters on the mechanical properties of the joints and determine the optimum welding parameters so as to obtain high-quality friction-stir-welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…However the stir zone experienced dynamic recrystallization during FSP. Some previous studies [13][14][15] showed that the as-stirred specimens contained grains of high dislocation density. If the dislocation density of the grains in the interior of a material affects the slope value, the effect of dynamic recrystallization on the k y value needs to be examined.…”
Section: Introductionmentioning
confidence: 89%
“…Some other studies 15,18) have shown that dynamic recrystallization which occurs during FSP often leaves some grains with a high density of dislocations in the stir zone. This result suggests …”
Section: Moving Directionmentioning
confidence: 98%
“…2,3) Recently, a new solid-state joining technology of the friction stir spot welding (FSSW), which is a derivative process of the friction stir welding (FSW), 4) has been developed as a widespread technique and successfully applied for producing lap-joints of aluminum alloys. [5][6][7] Compared with the traditional RSW process, FSSW can avoid severe heating and cooling cycles induced during welding process. Furthermore, the heat affected zone (HAZ) and residual stresses associated with the welds are relatively small.…”
Section: Introductionmentioning
confidence: 99%